Moderation of the association between childhood maltreatment and Neuroticism by the corticotropin-releasing hormone receptor 1 gene - DeYoung, Colin G. (2011)
BACKGROUND: Neuroticism is a personality trait reflecting the tendency to experience negative affect. It is a major risk for psychopathology, especially depression and anxiety disorders. Childhood maltreatment is another major risk factor for psychopathology and may influence personality. Maltreatment may interact with genotype to predict developmental outcomes. Variation in three polymorphisms of the CRHR1 gene has been found to moderate the association of childhood maltreatment with depression, and we hypothesized that it would also be linked to Neuroticism. METHODS: Variation in three CRHR1 SNPs (rs110402, rs242924, rs7209436) was assessed in 339 maltreated and 275 demographically similar nonmaltreated children, who participated in a day camp research program. Maltreated children were further categorized based on the number of types of maltreatment they had experienced and the most severe form of maltreatment experienced. Genotype and maltreatment status were used to predict the Big Five personality traits, as assessed by camp counselors following a week of interaction with children. RESULTS: CRHR1 genotype significantly moderated the association of maltreatment with Neuroticism but none of the other traits. Having two copies of the TAT haplotype of CRHR1 was associated with higher levels of Neuroticism among maltreated children relative to nonmaltreated children, with the exception of sexually abused children and children who had experienced 3 or 4 types of abuse. Effects sizes of these interactions ranged from η(2) = .01 (p = .02) to η(2) = .03 (p = .006). CONCLUSIONS: Variation in CRHR1 moderates the association of maltreatment with Neuroticism. The effects of specific types of maltreatment on Neuroticism are differentially moderated by CRHR1 genotype, as are the effects of experiencing more or fewer types of maltreatment.